Extracorporeal shock wave lithotripsy is safe and effective for pediatric patients with chronic pancreatitis - Wang, Dan; Bi, Ya-Wei; Ji, Jun-Tao; Xin, Lei; Pan, Jun; Liao, Zhuan; Du, Ting-Ting; Lin, Jin-Huan; Zhang, Di; Zeng, Xiang-Peng; Ye, Bo; Zou, Wen-Bin; Chen, Hui; Xie, Ting; Li, Bai-Rong; Zheng, Zhao-Hong; Li, Zhao-Shen; Hu, Liang-Hao (Endoscopy, 2017)
Background and aims Pancreatic extracorporeal shock wave lithotripsy (P-ESWL) is recommended as the first-line treatment for pancreatic stones. However, how well P-ESWL performs in pediatric patients remains unclear. We aimed to evaluate the safety and efficacy of P-ESWL for pediatric patients with chronic pancreatitis. Methods This prospective observational study was conducted in patients with painful chronic pancreatitis who underwent P-ESWL. Patients aged under 18 years were included in the pediatric group; patients aged over 18 years who underwent P-ESWL in the same period were assigned to the control group. For investigation of long-term follow-up, the pediatric group were matched with patients from the control group in a 1:1 ratio. The primary outcomes were P-ESWL complications and pain relief. The secondary outcomes included: stone clearance, physical and mental health, quality of life score, and growth and developmental state. Results From March 2011 to March 2015, P-ESWL was performed in 1135 patients (72 in the pediatric group, 1063 in the control group). No significant differences were observed in the occurrence of P-ESWL complications between the two groups (11.1 % vs. 12.8 %; P = 0.68). Among the 67 pediatric patients (93.1 %) who underwent follow-up for 3.0 years (range 1.3 – 5.2), complete pain relief was achieved in 52 patients (52 /67; 77.6 %); this value was not significantly different from that of the matched controls (55 /69; 79.7 %; P = 0.94).Conclusions P-ESWL is safe and effective for pediatric patients with chronic pancreatitis. It can promote significant pain relief and stone clearance, and can benefit growth and development.